Characterization of calcination temperature on a Ni-substituted lanthanum-strontium-zirconate pyrochlore. Issue 18 (15th December 2017) - Haynes, Daniel J.; Shekhawat, Dushyant; Berry, David A.; Zondlo, John; Roy, Amitava; Spivey, James J.
Abstract: A lanthanum strontium zirconate pyrochlore material was substituted with Ni, and the effect of calcination temperature on important catalytic properties was evaluated. The introduction of the Ni into the pyrochlore decreased the BET surface as compared to non-Ni containing materials due to enhanced sintering. The presence of Ni dispersed in the precursor material produced oxygen vacancies which improved solid state diffusion of the pyrochlore cations, and lowered the onset of crystallization by almost 100 °C compared to the baseline material without Ni. Furthermore, only a small amount of Ni was found to be soluble in the structure up to 1000 °C, at which point almost no Ni occupies lattice positions in the pyrochlore crystal structure. The Ni was found to exsolve to the surface and grain boundary regions of the pyrochlore and reside on the surface as NiO. Heating to temperatures greater than 800 °C also led to the formation of a La2 ZrNiO6 perovskite phase. Surface composition, as measured by XPS, showed a decrease in Ni concentration at the surface as the calcination temperature was increased. This was likely due to the formation of larger Ni particles with increasing temperature, as well as the migration of the Ni into the bulk through the formation of the La2 ZrNiO6 phase. Temperature programmed reduction results showed that increasing the calcination temperature resulted in particle growth of the NiO and a weaker interaction with the pyrochlore surface, which made the NiO more reducible at lower temperatures. Multiple reduction-oxidation TPR/TPO cycles showed that the results were not reproducible from cycle-to-cycle for the lowest calcination temperature material (700 °C) due to an amorphous La-Zr-O phase initially present. However, materials calcined at all other temperatures showed an almost identical TPR/TPR profiles after the second cycle.